MARKETING AUDIT AS A TOOL OF MARKETING ANALYTICS - Valentyna Litynska (Соціальна економіка)
The article systematizes the existing approaches to the interpretation of the concept of «marketing audit». In particular, scientists study marketing audit depending on the analysis process, research method, analysis tool, content of marketing diagnostics, management process. In addition, the factors that have a significant impact on the definitions of «marketing audit» are identified: speed of change, digital transformation, customer focus, integrated approach, data analysis.